Polymerase Chain Reaction (PCR) Positivity of COVID-19 reported in Teaching Hospitals of Rawalpindi Medical University Pakistan - Shahid, Rizwana; Khan, Muhammad Mujeeb; Rauf, Fatima; Chaudhary, Rija Farrukh; Afzal, Sheema; Umar, Muhammad; Zeb, Shazia (Infectious Diseases Journal of Pakistan, 2022)
Objective: To determine the PCR positive rate of COVID-19 in teaching hospitals of Rawalpindi Medical University amid COVID pandemic. Material & Methods: A cross-sectional hospital data based research was carried out by retrieving records of PCR tests done pertinent to COVID-19 in Holy Family Hospital and Benazir Bhutto Hospital Rawalpindi affiliated with Rawalpindi Medical University during 2020. Month wise data regarding PCR results was gathered from April – December 2020 and May –December 2020 from Holy Family Hospital and Benazir Bhutto Hospital Rawalpindi respectively. The data was analyzed by means of Microsoft Excel 2010. PCR positivity rates of both hospitals were calculated. Results: Total 76, 663 PCR tests were done in RMU affiliated teaching hospitals during 2020. PCR positive rates of Holy Family Hospital and Benazir Bhutto Hospital were determined to be 15.2% and 6.1% respectively. The highest percentage of PCR positive patients at Holy Family Hospital was reported during May followed by November 2020. On the other hand, the peak of PCR positivity at Benazir Bhutto Hospital was revealed during May-June 2020. Conclusion: Teaching hospitals are managing most of the public for their health problems. PCR positive rates reported in these healthcare facilities reflect the tangible picture of COVID-19 prevailing in general public. Keywords: PCR positivity, COVID-19, teaching hospitals.